EFEKTIVITAS PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK DENGAN MEDIA GAMBAR UNTUK KELAS V (STUDI PADA SISWA KELAS V SDN PADENGANPLOSO I PUCUK LAMONGAN) - PRIYANTO, BUDI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In the implementation of physical education in schools of learning in general is still very dominant role of the teacher so that students only receive a lesson and they can not learn in accordance with its development stage. Therefore it needs to be given a more varied learning models such as, providing learning with media images so that students are expected to play an active role in any learning process. In the process of learning a teacher can use the media as a means to convey information or materials so that materials may be accepted or absorbed by the students. Messenger (media) interact with students through their senses. Students are stimulated by the media was to use his senses to receive information. Sometimes students are required to use a combination of multiple senses in order to receive the message in full. The purpose of this study was to determine: (1) increase the learning effectiveness of the long jump with a squat-style media images, (2) large increase in the effectiveness of learning long jump squat style with media images. Objectives of this study is a class V student of SDN Padenganploso I Pucuk Lamongan and number of samples taken by 18 students. The method in this analysis using statistical methods and quantitative comparative desikriptif. Conclusions are as follows: (1) There is a long jump to increase the effectiveness of learning style squat with media images. Thoroughness of student learning outcomes during the 4 meetings has increased, with an average increase of 6.1%. (2) Long jump squat-style learning with media images provide improved performance was the long jump squat style of students at 12.50%. T test analysis results obtained: the tcount 5.00> 2.11 Ttable value. Keywords: Media image, Effectiveness learning, Long jump